2016
DOI: 10.1515/bjdm-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Examination of natural tooth color distribution using visual and instrumental shade selection methods

Abstract: Aim:Although visual color determination is the most frequently applied method in dentistry, instrumental color analysis offers advantages like objectivity, measurability and rapidity. The aim of this study was to evaluate the natural teeth color in teeth without any restoration visually, and by using a computerized shade measuring and analyzing system in the population.Materials and Methods: 202 patients were inspected. Before instru mental shade matching visual matching was done by the inspector with Vitapan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In dentistry, accurate and predictable shade matching between natural teeth and restorative materials represents a challenge for clinicians and laboratory technicians. For decades, visual shade matching was most commonly used for the shade selection in the dental clinics as it is easy and does not require expensive equipment 1,2 . Several studies reported that the color of the shade tabs is uniformly distributed and the shade guide enables accurate shade matching with the natural teeth 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…In dentistry, accurate and predictable shade matching between natural teeth and restorative materials represents a challenge for clinicians and laboratory technicians. For decades, visual shade matching was most commonly used for the shade selection in the dental clinics as it is easy and does not require expensive equipment 1,2 . Several studies reported that the color of the shade tabs is uniformly distributed and the shade guide enables accurate shade matching with the natural teeth 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…As proven by several studies, [21][22][23][24][25][26][27][28] the spectrophotometer used in the present study was found to be consistent and more objective than the visual shade guides and helped eliminate the effect of different light sources and inter examiner bias.…”
Section: Discussionmentioning
confidence: 53%
“…14,16,19 Several color space systems are available to describe color, with the Munsell and CIE systems being the most widely used, the Munsell system describes color in three dimension using three coordinates, the hue, value, and chroma, on the other hand, the CIE system uses three coordinates, L* a* b*, to describe color where L* is the lightness axis from black to white, a* is the red-green axis, b* is the yellow-blue axis, and ΔE is the color difference value that represents the color perception; only ΔE values between 1 and 2 are considered clinically acceptable, whereas values above or less than these would implicate a high degree of intra-and interexaminer variability, and render the use of digital shade matching devices more useful to minimize the subjectivity of color assessment. [20][21][22][23][24][25][26][27][28][29] Gingival color was found to be related to gender, age, and skin color of different ethnic origins, however, very little data exists regarding the color relation between the gingiva and the teeth. [30][31][32][33] Different gingival colors and pigmentations, and inadequacy of available gingival visual shade guides further complicate the situation and hinder the clinician from further investigations into pink esthetics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since the thickness of the layers is not constant along the entire tooth structure, but it varies according to the different tooth areas [7], it creates a color variation (gradient) along the different axis of the natural dental structures. These color variations within dental structures [8][9][10][11] are very difficult to measure with conventional devices used in clinical scenarios, which usually determine color by single spot measurements or large integrating measuring areas.…”
Section: Introductionmentioning
confidence: 99%